Platelet-to-lymphocyte, neutrophil-to-lymphocyte and lymphocyte-to-monocyte ratios are related to cancer-related fatigue and quality of life in patients with cancer: a cross-sectional study - Xianwu Luo; Bing Xue; Pei Fang; Xianmei Meng; Huidan Yu; Lanhui Tan; Ling Feng (BMJ Open)
Objectives To explore the association of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR) with cancer-related fatigue (CRF) and quality of life (QOL) in cancer patients.Design A cross-sectional study.Settings A grade A tertiary hospital in Wuhan, China.Participants A total of 236 participants were recruited. Participants who were diagnosed with cancer received chemotherapy and/or radiotherapy, and aged ≥18 years were included in this study.Primary and secondary outcome measures The PLR, NLR and LMR were calculated based on the absolute lymphocyte count, neutrophil count, platelet count and monocyte count. The CRF and QOL of patients after the first chemotherapy/radiotherapy were evaluated.Results The median values (IQR) of PLR, NLR and LMR were 174.51 (126.14–261.02), 2.84 (1.64–5.24) and 2.56 (1.30–3.72), respectively. Univariate analysis indicated that high PLR (≥ 174.51), high NLR (≥ 2.84) and low LMR (< 2.56) at baseline significantly correlated with CRF and poor QOL after the first chemotherapy/radiotherapy (p<0.005). Multiple linear regression analysis indicated that elevated PLR might be an independent risk factor for CRF (p<0.001) and QOL (p=0.010) in cancer patients.Conclusion PLR, NLR and LMR are associated with CRF and QOL in cancer patients. High PLR may predict severe CRF and poor QOL. Further studies are needed to validate these findings based on the expanded sample size.